Effect of Reinforcement Content and Cutting Parameters on Tool Wear in Machining of Aluminum Hybrid Composites - I. Sarpkaya; E. Özer; D. Zalaoğlu; M. Übeyli; Y. Fedai (Archives of Metallurgy and Materials)
The machinability of aluminum hybrid composites (AHCs) can be enhanced by utilization of optimum composition and cutting parameters. In this study, the machinability of AHCs containing micron-sized TiB2 and B4C particles was investigated using the face milling operation with a double coated cemented carbide tool. The composites, fabricated via cold pressing and microwave sintering, were subjected to the face milling experiments using a CNC milling machine. The influence of hybrid reinforcement content, feed rate and cutting speed on tool wear and surface roughness was examined during the milling of these composites. After the machinability tests, the worn surface of inserts was examined by a scanning electron microscope to see the wear types. The reinforcement content and cutting speed were obtained to have a much greater effect on the machinability and surface roughness of the hybrid composites compared to the feed rate. Either increasing the feed rate or decreasing the cutting speed provided a larger amount of chip removal until the wear limit. Moreover, the feed rate was obtained to be more effective on the tool wear at lower cutting speeds and higher amounts of hybrid reinforcement.